METHOD OF BODY VAVE MAGNITUDE CLARIFICATION FOR CARPATHIAN REGION EARTHQUAKES - NAZAREVYCH, L.; KENDZERA, O.; NAZAREVYCH, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The analysis of frequency composition of seismic vibrations (body waves) depending on magnitude of earthquake have been realized. On this basis the formulas for consideration of average frequency amendments for magnitude of earthquakes of the Carpathians region of Ukraine are definite. By the result of comparative analysis it is shown, that magnitude of weak Carpathians earthquakes in reality (taking into account frequency composition of seismic vibrations) are substantially greater, than are those, which are determined earlier using the simplified method without taking such into consideration.